Influence intra-blogosphérique et visibilité sur les réseaux sociaux - Damien Renard (Netcom)
The study aims to better understand who the influential blogger within the territory of cooking blogs are. We build a model to observe the influence process, from the analysis of blogger’s influence in his virtual community until the diffusion on social networks. From the quantitative analysis of 952 blogs, we show that blogger’s role in his virtual community determines his own activity of publications but also his influence on social networks.